Control de las finanzas por medio de las planificaciones presupuestarias en la Compañía Transutah de la ciudad de Guayaquil Provincia del Guayas - Fernandez Herrera, Jorgely Adriana (2021)
The investigation considers the impact that the lack of budget planning has within the financial information, the main problem of the company being the non-use of an annual budget, which helps them to know their projections in both sales and purchases, to be able to have a contingency plan for problems that may arise during the process of activities in the fiscal year. These incidents were analyzed within the transport company Transutah SA, which is located in the city of Guayaquil, focusing on the 2020 period, using as a source of information, the collection of information obtained from the questions made to the manager. and the accountant of the same, in addition to the information provided by them, on the financial statements, this is done in order to find the critical areas, where special evaluations must be carried out so that the decision-making of the administrative part is timely. As a result, the non-budget planning of the company's departments can be demonstrated, it does not allow it to be structured in the best way, helping within the processes.